MEASURING AID EFFECTIVENESS: AN ANALYSIS OF BENEFICIARY PERSPECTIVES - Yahaya, B. I.; Yakubu, B. I. (UDS International Journal of Development, 2016)
The study Ghana sought to contribute to the subject of aid effectiveness by exploring the potential added value of including beneficiary perspectives. The study was motivated by the fact that most evaluation of the effectiveness of development aid tend adopt a top-down approach without seeking to address beneficiary perspectives as a major factor in impact evaluation of development interventions The study which was conducted in the Tamale metropolis, adopted qualitative methods. Focus group discussions were conducted in eight communities. Additional data was collected by means of key informant interviews. The results were revealing as it showed clearly that beneficiaries are as concerned as donors regarding how aid is applied. Beneficiaries have a clear understanding of aid effectiveness and are able to illustrate vividly their perception on the subject. Much as beneficiaries have clear ideas regarding their role in ensuring aid effectiveness they are constrained by cultural, social and lack of appropriate institutional structures for channeling their concerns on the activities of NGOs. Consequently, beneficiaries feel left out of efforts by civil society aimed at ensuring effective aid delivery. A key recommendation resulting from the study is that impact of development interventions could be improved significantly if the views of beneficiaries on project impact are taken into consideration earlier during project implementation rather than capturing them at the end of project implementation as unintended outcomes. This, in turn, calls for some degree of flexibility from donors in modifying their expectations Keywords: Aid effectiveness, development aid, beneficiaries, NGOs